Self-Compacting Concrete Using GBPS with Addition of Steel Fibers on M30 Grade of Concrete (International Journal of Innovative Research in Computer Science & Technology, 2023)
Self-compacting concrete has emerged as  a creative invention that is capable of solving the problem  and making a remarkable advancement in the field of  substantial innovation, which has led to the prior practise  of substantial design free from vibration. Self-compacting  concrete use today is focused on higher performance,  better and more solid quality, and uniformity. Self compacting concrete (SCC) with GGBS and blended steel  strands is being created in this research. The goal of this  work is to create M30 SCC with GGBS cream steel fibers  and compare its strength to normal concrete. The IS  10262 2009 standard is used to produce regular cement,  whereas the alter Nan Su approach is used to produce  SCC. In order to increase the volume of cement, the  significant is replaced by 0, 10, 20, 30, and 40% of GGBS  with the addition of stable steel strands at a 0.5%  expansion. The compressive strength of SCC is  determined using 3D squares of size 150x150x150mm,  while the split tensile strength is determined using  cylinder-shaped examples of size 150x300mm, and the  flexural strength of SCC is determined using crystals of  size 100x100x500mm.
Keywords: Ground granulated blast boiler slag; self-compacting concrete (SCC); FA (fine aggregate); CA (coarse aggregate); and OPC (ordinary portland cement)